Pertanggungjawaban Pidana Terhadap Distributor Rokok Illegal - Arin Vevi Putri Ayu Hermawan (TERAJU: Jurnal Syariah dan Hukum, 2025)
The circulation of illegal cigarettes by distributors in Indonesia is a serious problem and has a negative impact on many aspects, including the national economy, industry, and general health. The increasing prevalence of illegal cigarettes in circulation can cause state excise revenue to decrease. A number of products that are taxed in this context include tobacco, and the largest product is cigarettes. Cigarettes are a processed tobacco product that is popular among the public. With a large number of users and high excise implementation, this has led to the emergence of individuals who take advantage of avoiding paying excise. This research aims to analyse criminal acts related to the circulation of illegal cigarettes and the criminal liability of illegal cigarette dealers. The method used is the normative juridical method through its approach to the rules of Law Number 39 of 2007 and legal analysis to understand the process of criminal liability for the circulation of illegal cigarettes. The findings of the study indicate that criminal liability for the circulation of illegal cigarettes in Indonesia is very clearly regulated through the Excise Law, the norm contained is that every person who produces, distributes, or sells cigarettes without a valid excise sticker will be subject to imprisonment and fines. The resulting findings are expected to clearly illustrate criminal liability for the circulation of illegal cigarettes in Indonesia.